CIRCUMSTANTIAL EVIDENCE AS SYSTEM ACTUALIZATION PROOF OF CRIMINAL HARASSMENT IN SCOPE CORPORATION - Muhammad Rifqi (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2023)
Based on the results of a survey by the Never Okay Project, 70.81% of respondents have been victims of violence and harassment in the world of work. This is because there is no specific regulation that becomes a legal umbrella in cases of harassment in the corporate sphere. The rigid evidence system in Indonesia is also the reason for the increase in casualties. Circumstantial Evidence as a criminal proof system in cases of harassment carried out within the corporate scope is urgent because the protection of victims of harassment can be improved by showing a relationship between facts or events related to harassment behavior. This research uses a juridical-normative approach method, which focuses on analyzing legal norms contained inside or outside laws and regulations. This study concludes that the protection of workers victims of harassment in the corporate sphere is still minimal, so it requires specific legal regulations governing the prevention, handling, and protection of victims. In addition, more rigid regulations are needed regarding the use of Circumstantial Evidence as evidence in cases of harassment within the corporate sphere, by formulating clear guidelines or provisions in the criminal procedure law.